2023
DOI: 10.3390/pathogens12070934
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Rotavirus C from Rescued Sloth Bears, India: Evidence of Zooanthroponotic Transmission

Abstract: The present study reports the detection and molecular characterisation of rotavirus C (RVC) in sloth bears (Melursus ursinus) rescued from urban areas in India. Based on an RVC VP6 gene-targeted diagnostic RT-PCR assay, 48.3% (42/87) of sloth bears tested positive for RVC infection. The VP6, VP7, and NSP4 genes of three sloth bear RVC isolates (UP-SB19, 21, and 37) were further analysed. The VP6 genes of RVC UP-SB21 and 37 isolates were only 37% identical. The sequence identity, TM-score from structure alignme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Their tests revealed the presence of Crimean–Congo hemorrhagic fever virus (CCHFV) and WNV in the African tick Hyalomma rufipes [ 5 ]. In India, Singh Malik et al reported the detection and characterization of the rotavirus C genome in sloth bears ( Melursus ursinus ) residing in urban areas, possibly originating from pigs or humans [ 6 ].…”
mentioning
confidence: 99%
“…Their tests revealed the presence of Crimean–Congo hemorrhagic fever virus (CCHFV) and WNV in the African tick Hyalomma rufipes [ 5 ]. In India, Singh Malik et al reported the detection and characterization of the rotavirus C genome in sloth bears ( Melursus ursinus ) residing in urban areas, possibly originating from pigs or humans [ 6 ].…”
mentioning
confidence: 99%